The Effect of Slope on the Infiltration Capacity and Erosion of Mount Merapi Slope Materials - Adam Pamudji Rahardjo; Anselma Diksita Prajna Duhita; Ani Hairani (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
The infiltration on slopes has a specific behavior capable of being parameterized and one of the reasons is due to the ability of the slope to generate less ponding on the sloping soil surface. This, therefore, affects infiltration rate and surface runoff proportion of water from any kind of rainfall distribution and the tendency of the surface runoff to be higher usually leads to a higher erosion rate on the slope. Moreover, slope steepness is the most important parameter of a slope, and its effect at 36%, 47%, and 58% was tested on the infiltration capacity and erosion rate of Mt. Merapi bare slope material in a laboratory using a rainfall simulator. The rainfall intensity was set constant at a rate of 116.31 mm/hour while the infiltration rate was measured by the volumetric balance principle and the erosion rates by collecting the eroded grains at the downstream end flume. Furthermore, the infiltration capacity was evaluated using the Horton method by fitting the equation to the recorded infiltration rate data while the average erosion was through the eroded grain data for each test. The results obtained represent the relationship between slope steepness, the affected infiltration capacity, and erosion for each test, and the infiltration capacity was found to be decreasing in lower slope < 47% and increasing in a higher slope while the erosion rate was increasing between 7% and 15% for each 1% increase in the slope steepness. In addition, polynomial and linear equations were developed to express the relationship between these three indicates at the Mt. Merapi bare slope material.